2022
DOI: 10.1007/s00384-022-04183-x
|View full text |Cite
|
Sign up to set email alerts
|

High complication rate in Crohn’s disease surgery following percutaneous drainage of intra-abdominal abscess: a multicentre study

Abstract: Introduction Intra-abdominal abscesses complicating Crohn’s disease (CD) present an additional challenge as their presence can contraindicate immunosuppressive treatment whilst emergency surgery is associated with high stoma rate and complications. Treatment options include a conservative approach, percutaneous drainage, and surgical intervention. The current multicentre study audited the short-term outcomes of patients who underwent preoperative radiological drainage of intra-abdominal abscesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However, this therapeutical concept is rather good clinical practice than evidence-based medicine since high-quality studies such as prospective randomized studies are still lacking. Furthermore, the benefit of percutaneous drainage is still in discussion as recently published studies have presented conflicting results [ 12 , 13 , 14 ]. Therefore, antibiotics still play a fundamental role in intra-abdominal abscess formations in CD to prevent further septic complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, this therapeutical concept is rather good clinical practice than evidence-based medicine since high-quality studies such as prospective randomized studies are still lacking. Furthermore, the benefit of percutaneous drainage is still in discussion as recently published studies have presented conflicting results [ 12 , 13 , 14 ]. Therefore, antibiotics still play a fundamental role in intra-abdominal abscess formations in CD to prevent further septic complications.…”
Section: Introductionmentioning
confidence: 99%
“…The safety and effectiveness of image-guided PD as a treatment for anastomotic leak following colorectal surgery have been previously analyzed [ 20 ]. Specifically in CD patients, the percutaneous procedure is indicated in the guidelines in case of a preoperative diagnosis of an abscess, in order to postpone surgery and reduce the risk of extensive resection and intraoperative complications [ 21 , 22 , 23 , 24 ]. However [ 24 ], there has been a lack of reports in the literature regarding the outcomes of the procedure as a primary treatment for anastomotic leak after surgery for CD [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Celentano et al showed that CD patients who required PIGD of intra-abdominal abscesses are at increased risk of postoperative morbidity and septic complications following ileocaecal or re-do ileocolic resection compared with patients who did not require drainage. 113 Nevertheless, it is important to clarify that this study did not compare surgical outcomes in patients who underwent primary surgical drainage and anastomosis. This study revealed a significantly higher postoperative morbidity in the group of patients who underwent preoperative PIGD (44.4 vs. 23.4%), including a higher rate of wound infection (8.3 vs. 3.3%) and anastomotic leak (11.1 vs. 2.6%).…”
Section: Crohn's Diseasementioning
confidence: 97%
“…The authors suggested that the increased risk of postoperative morbidity in these patients could be partially explained by the fact that they demonstrated a higher rate of risk factors for postoperative complications, including recurrent disease, penetrating disease, and the need for preoperative total parenteral nutrition. 113 Additionally, these patients likely did not have their anti-inflammatory medical therapies restarted between drainage and surgery, which has been shown to be a major benefit of PIGD in this setting.…”
Section: Crohn's Diseasementioning
confidence: 99%